2013
DOI: 10.1073/pnas.1220591110
|View full text |Cite
|
Sign up to set email alerts
|

Reinstatement of nicotine seeking is mediated by glutamatergic plasticity

Abstract: Nicotine abuse and addiction is a major health liability. Nicotine, an active alkaloid in tobacco, is self-administered by animals and produces cellular adaptations in brain regions associated with drug reward, such as the nucleus accumbens. However, it is unknown whether, akin to illicit drugs of abuse such as cocaine or heroin, the adaptations endure and contribute to the propensity to relapse after discontinuing nicotine use. Using a rat model of cue-induced relapse, we made morphological and electrophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
268
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(282 citation statements)
references
References 40 publications
11
268
3
Order By: Relevance
“…It was shown for instance that repeated treatments with drugs of abuse known to enhance brain stimulation reward alter the expression of GluN2A and GluN2B, and their respective mRNA, in different limbic brain regions (Barr et al, 2014;Gipson and Reissner, 2013;Kindlundh-Högberg et al, 2008). Carlezon et al, (2001) compared the expression of GluN1 in the ventral tegmental area between rats that self-stimulated for one hour consecutively and rats that received no stimulation and found no difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown for instance that repeated treatments with drugs of abuse known to enhance brain stimulation reward alter the expression of GluN2A and GluN2B, and their respective mRNA, in different limbic brain regions (Barr et al, 2014;Gipson and Reissner, 2013;Kindlundh-Högberg et al, 2008). Carlezon et al, (2001) compared the expression of GluN1 in the ventral tegmental area between rats that self-stimulated for one hour consecutively and rats that received no stimulation and found no difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…This glial function is required for the fidelity of glutamatergic synaptic communication and protection from excitotoxicity, since GLT-1 is responsible for more than 90% of uptake in the brain (Danbolt, 2001). Chronic exposure to several classes of addictive substances, including cocaine, nicotine, ethanol, and heroin, reduces expression of GLT-1 (Knackstedt et al, 2010a;Sari and Sreemantula, 2012;Gipson et al, 2013b;Shen et al, 2014b;Reissner et al, 2015). As such, GLT-1 downregulation may serve as a common drug-induced neuroadaptation contributing to relapse vulnerability.…”
Section: Glial Cellsmentioning
confidence: 99%
“…Selective depotentiation of PLC-to-NAcore projection using optogenetics reduced the incubation of cocaine seeking . Glutamate originating from the PLC was also shown to be necessary for cue-induced reinstatement of nicotine seeking and heroin seeking (LaLumiere and Gipson et al, 2013b). In addition, although direct projections have not yet been tested, both the PLC and NAcore are necessary for the cue-induced reinstatement of heroin, methamphetamine, ethanol, and 3,4-methylenedioxymethamphetamine seeking (Rogers et al, 2008;Chaudhri et al, 2010;Rocha and Kalivas, 2010;Ball and Slane, 2012;Willcocks and McNally, 2013).…”
Section: A Nucleus Accumbens Corementioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have mostly reported changes engendered by alcohol consumption and exposure, low-cost access to an improved proteomics will lead to detailed studies where proteomes from discrete brain subregions will be profiled with an increased sample number and during different time points after withdrawal. Indeed, recent evidences in rodent models have suggested that, at least for cocaine or nicotine, a longer withdrawal corresponds to a greater drug-seeking, which may imply greater potential for relapse vulnerability (Gipson et al, 2013;Ben-Shahar et al, 2013). Long-lasting changes in the proteome that persist after protracted withdrawal and likely relate to relapse liability would be of high interest to translational scientist.…”
Section: Future Research Directionsmentioning
confidence: 99%